2019
DOI: 10.1002/cnma.201800619
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nonblinking Cs4PbBr6 Nanoparticle as a Nanothermometer

Abstract: Inorganic perovskite materials have attracted broad interest in the last several years due to their stability and promising applications as photovoltaic and light‐emitting materials. In this work, we prepared Cs4PbBr6 nanoparticles showing stable photoluminescence (PL) without blinking and studied the PL properties of individual Cs4PbBr6 nanoparticles in the biological temperature range. We found that both PL intensity and lifetime of a single Cs4PbBr6 particle strongly depends on the temperature. The PL inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that the Cs 4 PbBr 6 showed a linear decrease of PL intensity along with the augment of temperature. [ 219 ] The slopes of the PL intensity versus temperature were as high as 2% per degree centigrade. The ultrahigh sensitivity of Cs 4 PbBr 6 proved it to be the most likely candidate for use in thermometers for thermal detection.…”
Section: Applicationsmentioning
confidence: 99%
“…It has been reported that the Cs 4 PbBr 6 showed a linear decrease of PL intensity along with the augment of temperature. [ 219 ] The slopes of the PL intensity versus temperature were as high as 2% per degree centigrade. The ultrahigh sensitivity of Cs 4 PbBr 6 proved it to be the most likely candidate for use in thermometers for thermal detection.…”
Section: Applicationsmentioning
confidence: 99%